ANALYSIS OF SPEECH ACTS IN DONALD TRUMP’S ACCEPTANCE SPEECH. - LOKO, Djima Crépin (My University, 2018)
This article aims at carrying out a pragmatic analysis of a selected extract from Donald Trump’s acceptance speech delivered at the Republican National Convention on July 21st, 2016. The study mainly focuses on the identification and the analysis of linguistic features of speech acts (Austin 1962 and Searl 1969) used in the political language of the acceptance speech to uncover the way Donald Trump has encoded his own intentions and his party’s expectations therein. The identification of illocutionary acts indicates the presence of representative acts, directive acts, expressive acts, commissive acts, and declarative acts. The interpretation of the findings reveals the dominance of representative illocutionary acts which shows that Trump has mainly expressed his personal beliefs, on the one hand, and displayed his truth engagement to lead his party to the White House, on the other. Directive illocutionary acts are used to suggest some solutions, while commissive acts are used to point out challenges of security and peace to be taken up once elected. As for expressive acts, they reflect Trump’s psychological state, while addressing the audience at the convention. The article concludes that the study of speech acts has made it easy to comprehend the message in President Donald Trump’s speech.
Keywords: Speech acts; Republican National Convention; Pragmatics; political